The natural history of protein domains. - Ponting, C; Russell, R (2002)
Genome sequencing and structural genomics projects are providing new insights into the evolutionary history ofprote in domains. As methods for sequence and structure comparison improve, more distantly related domains are shown to be homologous. Thus there is a need for domain families to be classified within a hierarchy similar to Linnaeus' Systema Naturae, the classification of species. With such a hierarchy in mind, we discuss the evolution of domains, their combination into proteins, and evidence as to the likely origin of protein domains. We also discuss when and how analysis of domains can be used to understand details of protein function. Unconventional features of domain evolution such as intragenomic competition, domain insertion, horizontal gene transfer, and convergent evolution are seen as analogs of organismal evolutionary events. These parallels illustrate how the concept of domains can be applied to provide insights into evolutionary biology.